121k views
0 votes
ANSWER ASAP!! Use the substitution method to solve the system of equations. 3x+7y=1 and y=x-7

User Nemmy
by
5.6k points

1 Answer

3 votes

Answer:

x=5

y = -2

(5,-2)

Explanation:

3x+7y=1 and y=x-7

Substitute the second equation in for y in the first equation

3x+7( x-7)=1

Distribute

3x+ 7x - 49 = 1

Combine like terms

10x - 49 =1

Add 49 to each side

10x-49+49 = 1+49

10x = 50

Divide by 10

10x/10 = 50/10

x = 5

Now find y

y = x-7

y = 5-7

y = -2

User GrumpyCrouton
by
5.3k points